Ice Hockey Summit II. Issue 2 (March 2015) - Smith, Aynsley M.; Stuart, Michael J.; Dodick, David W.; Roberts, William O.; Alford, Patrick W.; Ashare, Alan B.; Aubrey, Mark; Benson, Brian W.; Burke, Chip J.; Dick, Randall; Eickhoff, Chad; Emery, Carolyn A.; et al.
<x xml:space="preserve">Abstract</x> This study aimed to present currently known basic science and on-ice influences of sport-related concussion (SRC) in hockey, building upon the Ice Hockey Summit I action plan (2011) to reduce SRC. The prior summit proceedings included an action plan intended to reduce SRC. As such, the proceedings from Summit I served as a point of departure for the science and discussion held during Summit II (Mayo Clinic, Rochester, MN, October 2013). Summit II focused on 1) Basic Science of Concussions in Ice Hockey: Taking Science Forward, 2) Acute and Chronic Concussion Care: Making a Difference, (3) Preventing Concussions via Behavior, Rules, Education, and Measuring Effectiveness, 4) Updates in Equipment: Their Relationship to Industry Standards, and 5) Policies and Plans at State, National, and Federal Levels To Reduce SRC. Action strategies derived from the presentations and discussion described in these sectors were voted on subsequently for purposes of prioritization. The following proceedings include the knowledge and research shared by invited faculty, many of whom are health care providers and clinical investigators. The Summit II evidence-based action plan emphasizes the rapidly evolving scientific content of hockey SRC. It includes the most highly prioritized strategies voted on for implementation to decrease concussion. The highest-priority action items identified from the Summit include the following: 1) eliminate head hits from all levels of ice hockey, 2) change body checking policies, and 3) eliminate fighting in all amateur and professional hockey.